Cardiac arrhythmias associated with immune checkpoint inhibitors: A comprehensive disproportionality analysis of the FDA adverse event reporting system - Wang, Feifei; Wei, Qi; Wu, Xinan (Frontiers in Pharmacology, 2022)
Introdution: With the widespread application of Immune checkpoint inhibitors (ICIs), it is important to explore the association between ICIs and cardiac arrhythmias and to characterize the clinical features of ICI–associated cardiac arrhythmias in real-world studies. Objective: The purpose of this study was to characterize the main features of ICI-related cardiac arrhythmias. Methods: From January 2017 to June 2021, data in the Food and Drug Administration Adverse Event Reporting System (FAERS) database were retrieved to conduct the disproportionality analysis. For the ICI-related cardiac arrhythmia detection, signals were detected by reporting odds ratio (ROR) and information component (IC). The clinical characteristics of patients with ICI–related cardiac arrhythmias were compared between fatal and non-fatal groups, and the time to onset (TTO) following different ICI regimens was further investigated. Multivariate logistic regression was used to evaluate the association between concurrent cardiotoxicities and ICI-associated arrhythmias. Results: We identified a total of 1957 ICI–associated cardiac arrhythmias which appeared to influence more men (64.44%) than women (30.76%), with a median age of 68 (interquartile range [IQR] 60–75) years. Patients with lung, pleura, thymus and heart accounted for the largest proportion (38.02%). Compared with the full database, ICIs were detected with pharmacovigilance of cardiac arrhythmias (ROR025 = 1.16, IC025 = 0.19). Anti–PD–1 and anti–PD–L1 monotherapies were found to be related to arrhythmias, corresponding to ROR025 = 1.03, IC025 = 0.06 and ROR025 = 1.27, IC025 = 0.29, respectively, with the exception of anti–CTLA–4 monotherapies (ROR025 = 0.57, IC025 = -1.21). The spectrum of arrhythmias induced by ICIs differed among therapeutic regimens. There was no significant difference in the onset time between monotherapy and combination regimen. Moreover, ICI–associated arrhythmias were associated with other concurrent cardiotoxicity. Conclusions: ICI monotherapy and combination therapy can lead to cardiac arrhythmias that can result in serious outcomes and tend to occur early. Our findings underscore the importance of early recognition and management of ICI-related cardiac arrhythmias.